Organum: a escritura musical em “Pentágono de Hahn” de Osman Lins - Borges, Poliana Queiroz (2015)
The objective of this study is to analyze the musical correspondences in "Hahn's Pentagon," the third narrative of Nove, Novena (1966), by Osman Lins. This work from the author's transitional phase, introduces several poetic innovations such as the use of unpronounceable signs, that establishes a silence full of meaning. Consider them a stylized representation of the musical figures already established in the musical writing, too little for the attempted approximation of the two artistic languages, the musical and the literary. The proposal became effectively possible by approaching the musical parameters of the characteristics of the characters and their respective semantic fields. For the configuration of what is called "literary score", the first part of this dissertation is dedicated to the configuration of the space, the pentagon. This geometric figure revealed several symbolic and also musical representations, constituting the pentagram or the stave where the compositions are written. The concept of soundscape was added to the constitution of space, expanding the musical possibilities in the literary text. The organum as a manifestation of polyphony, was composed by five narrative voices in equivalence with the "movements" of a musical composition. For the analysis of the characters, besides the musical equivalents, references were used from the field of symbolic hermeneutics, through the elements observed in the text. The question of silence returns when we analyze the title character, because the animal condition of Hahn, is also an impediment to his speech. As a final approximation between the arts, we notice the similarity of the musical composition technique called fugue with the structure of the work, indicating the idea of a musical transcription for the literary text. In developing this study, we base ourselves on the considerations of Mario Praz, Etienne Souriau and GE Lessing, with regard to the correspondence between the arts. For the symbolic image analysis we make use of the reflections of Mircea Eliade, Gaston Bachelard and Joseph Campbell. Undertaking an incursion through the text in search of the author's intent in redimentioning his poetics, we intend to contribute with new approaches to the multiple techniques used by Lins, with the intention to attain the fullness of his writing.